Look for me a novel - Gardner, Lisa (New York, New York Dutton, an imprint of Penguin Random House LLC, 2018)
The home of a family of five is now a crime scene: four of them savagely murdered, one--a sixteen-year-old girl--missing. Was she lucky to have escaped the carnage? Or does her absence speak of something more sinister? Sergeant Detective D.D. Warren is on the case--but so is survivor-turned-avenger Flora Dane. Seeking different types of justice, they must make sense of the clues left behind by a young woman who, whether as victim or suspect, is silently pleading: Look for me--
106043
Keywords: Warren, D. D. -- (Fictitious character) -- Fiction; Police -- Massachusetts -- Boston -- Fiction; Murder -- Investigation; Young women; Missing persons; Dane, Flora (Fictitious character); Vigilantes; Fiction. -- Mystery & Detective -- Police Procedural; Boston (Mass.) -- Fiction; Mystery fiction; Suspense fiction; Fiction; Thrillers (Fiction); Detective and mystery fiction